Pengaruh masa simpan krim santan terhadap tingkat penerimaan panelis - Asriani I. Laboko (Fakultas Pertanian Universitas Ichsan Gorontalo, 2020)
Coconut (Nyiur) is a tall palm tree beach, a quite old plant, that mostly spread throughout the tropics, and at the beginning of the Christian era it was well known and utilized by people in daily life and subsequently people had been traded as merchandise to various places, both abroad such as India, Sri Lanka, or in domestically (Indonesia). This study aimed to determine the level of coconut milk cream storage on the aroma, color, and texture. This research was conducted by an experiment with 3 treatments and 3 replications. S1 = 15 g salt : 500 g coconut grated, S2 = 20 g salt : 500 g coconut grated, S3 = 25 g salt : 500 g coconut grated. These treatments were tested by organoleptic tests which included aroma, color, and texture with 25 panelists. The results showed that at 3 weeks of storage, those treatments had not been decay. The more salt adding to coconut milk cream, the slower the process of decay, which can be seen from the panelist preferred level and the treatment preferred by the panelists, as well as resistant to decay. It was showed by S2 treatment (20 g salt : 500 g coconut grated).